Flexible interconnected support for decarbonizing local energy systems with high penetration distributed energy resources and electric vehicles - Xuefei Zhang; Niancheng Zhou; Jianquan Liao; Qianggang Wang; Yiyao Zhou; Xiaolong Xu; Edris Pouresmaeil (International Journal of Electrical Power & Energy Systems)
As energy transition to low-carbon, resilient, and distributed models, the local energy systems (LES) integrated with low-carbon technologies are expected to play a key role in minimizing the impact of the energy transition on distribution grids and achieving local community carbon neutrality goals. However, the current LES faces the problem of low efficiency and voltage deviations, including undervoltage and overvoltage, due to the increasing amount of distributed energy resources (DERs) and peak loads caused by electrification. This paper proposes a flexible interconnection support device, which accounts for only 2% of the transmitted power, to ensure an efficient, high-quality, and reliable LES integrated with large-scale DERs and extreme peak loads. This device leads to a flexible construction of LES and improves the power supply quality for the extreme loads. Furthermore, the total line losses of the LESs can be reduced by optimizing the transmitted power of the device by utilizing a genetic algorithm. The performance of the proposed device is evaluated based on real-time data and compared with the conventional LES. The results confirm that the proposed flexible interconnection devices can significantly improve the voltage deviation problem of LES under high-power load changes, such as EVs, improve the penetration of large-scale DERs, and reduce the line losses of the system.